2013
DOI: 10.1016/j.pain.2013.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-mediated improvements in painful neuropathy associated with prediabetes in mice

Abstract: Recent research suggests that exercise can be effective in reducing pain in animals and humans with neuropathic pain. To investigate mechanisms in which exercise may improve hyperalgesia associated with prediabetes, C57Bl/6 mice were fed either standard chow or a high-fat diet for 12 weeks and were provided access to running wheels (exercised) or without access (sedentary). The high-fat diet induced a number of prediabetic symptoms, including increased weight, blood glucose, and insulin levels. Exercise reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
101
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 58 publications
16
101
2
Order By: Relevance
“…Nonetheless, this result suggests a salutary effect for exercise, and parallels rodent studies that find C57Bl/6 mice provided running wheel exercise avoid neuropathic pain associated with a high fat diet, even though they show no improvement in Metabolic Syndrome features. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this result suggests a salutary effect for exercise, and parallels rodent studies that find C57Bl/6 mice provided running wheel exercise avoid neuropathic pain associated with a high fat diet, even though they show no improvement in Metabolic Syndrome features. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been shown that long-term running at mod-102 erate intensity [5,23], contrary to short-term running [26], increased 103 GDNF concentration in the striatum and sciatic nerve. [27] and TNF-α production [28] The rats had free access to tap water and standard rat food (Javaneh [26].…”
mentioning
confidence: 99%
“…Reductions in IENFD correlate with small fiber damage and sensory neuropathies (Lauria et al., 1999; Pittenger et al., 2004). Previous work by our group and others has displayed that IENFD is altered by changes in diet and exercise (Callaghan et al., 2016; Groover et al., 2013; Smith et al., 2006). Here, female LCR rats demonstrated a significant increase in the density of PGP‐9.5 + intraepidermal nerve fibers compared to HCR rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall percentage of TrkA fibers was similar between groups. Studies have established allodynia and reduced mechanical thresholds are associated with increased TrkA fibers (Cheng, Dauch, Hayes, Hong, & Feldman, 2009; Cheng, Dauch, Hayes, Yanik, & Feldman, 2012; Groover et al., 2013). This increase in IENF and increase in TrkA+ fiber density may predict that LCR rats display a greater response to evoked allodynia and are at risk for longer duration of heightened sensitivity.…”
Section: Discussionmentioning
confidence: 99%